Researcher or Teacher? Study of the Relationship between the Teaching Commitment and Research Activity of Doctoral Students - Shelest, Olena (Studia Oeconomica Posnaniensia, 2017)
The aim of this paper is to analyze the level of doctoral students' involvement in teaching and research and to examine the scope and direction of the interaction between these two areas. The theoretical part of the article provides a literature review. The empirical part of the paper focuses on the data that are a part of the survey conducted among academic teachers and doctoral students affiliated with the Poznań University of Economics and Business. The analysis leads to the conclusion that doctoral students are primarily concerned with research-related activities. In addition, the study revealed a negative relationship between the amount of time spent on teaching work and the effects of scientific activity.